The potential for short term deployment of carbon dioxide utiltisation technology in the European steel industry - Hall, Callum (2016)
The following EngD thesis presents research on the potential for short term deployment of carbon dioxide utilisation technologies within the context of the European steel industry, in collaboration with Tata Steel Europe. The aim of the project was to identify options for short term utilisation of CO2 directly from steelmaking process exhausts and then evaluate them in terms of their technical feasibility, CO2 reduction potential and economic sustainability. An initial review of steel production processes and CDU routes resulted in the selection of two potentially promising processes for further investigation; production of precipitated calcium carbonate (PCC) from steelmaking wastes, and combined biomass production and steelmaking wastewater remediation using microalgae. Each technology was investigated experimentally to determine its technical feasibility, and then via a techno-economic evaluation in order to estimate the scale of potential CO2 mitigation and economic viability. Although both technologies were deemed to be technically feasible, when techno-economic evaluations were performed it became clear that neither technology is likely to be able to achieve significant CO2 emissions reductions (reduction is limited to less than 1% of typical integrated site emissions). Despite this, economic estimates for a scaled up PCC production process were promising; a moderate payback on capital expenditure of around 5.51 years was estimated under baseline conditions, with a significant additional revenue potential if the process were credited under the European Union Emissions Trading Scheme. In contrast, the microalgae based process was found to be highly uneconomical when using technology which is currently available at a commercial scale, and the CO2 mitigation potential was determined to be limited by the indirect CO2 emissions from very high electricity demands as the process is scaled up.